Neuronal guidance molecules in bone remodeling and orthodontic tooth movement - Şen, Sinan; Erber, Ralf (International journal of molecular sciences, 2022)
During orthodontic tooth movement, mechanically induced remodeling occurs in the alveolar bone due to the action of orthodontic forces. The number of factors identified to be involved in mechanically induced bone remodeling is growing steadily. With the uncovering of the functions of neuronal guidance molecules (NGMs) for skeletal development as well as for bone homeostasis, NGMs are now also among the potentially significant factors for the regulation of bone remodeling during orthodontic tooth movement. This narrative review attempts to summarize the functions of NGMs in bone homeostasis and provides insight into the currently sparse literature on the functions of these molecules during orthodontic tooth movement. Presently, four families of NGMs are known: Netrins, Slits, Semaphorins, ephrins and Eph receptors. A search of electronic databases revealed roles in bone homeostasis for representatives from all four NGM families. Functions during orthodontic tooth movement, however, were only identified for Semaphorins, ephrins and Eph receptors. For these, crucial prerequisites for participation in the regulation of orthodontically induced bone remodeling, such as expression in cells of the periodontal ligament and in the alveolar bone, as well as mechanical inducibility, were shown, which suggests that the importance of NGMs in orthodontic tooth movement may be underappreciated to date and further research might be warranted.
Gesehen am 17.10.2022